Chronic ethanol exposure reduces the expression of NCX3 in the hippocampus of male C57BL/6 mice. Issue 6 (10th April 2019) - Wang, Changliang; Wang, Xiaolong; Li, Yan; Xia, Zhixiu; Liu, Yang; Yu, Hao; Xu, Guohui; Wu, Xu; Zhao, Rui; Zhang, Guohua
Abstract : Chronic ethanol (EtOH) exposure can cause intracellular Ca 2+ overload by stimulating calcium channel receptors and trigger apoptosis of neurons. NCX3 may play a cytoprotective role in intracellular Ca 2+ excretion. In this study, the effect of EtOH on NCX3 was analyzed by observing NCX3 expression in the hippocampus of chronic EtOH-exposed male C57BL/6 mice. Mice were divided into a control group, a 10% EtOH group, and a 20% EtOH group for 30, 60, and 90 days. Behavioral changes were observed using the Morris water maze. The protein and mRNA expressions of NCX3 and their distribution in the hippocampus were observed by western blotting, quantitative PCR, and immunohistochemistry staining. The results showed that EtOH exposure exerted a significant adverse effect on the spatial memory capacity of mice. Increased expression of calpain-1 and cleaved caspase-3 proteins indicated increased apoptosis. The expression of NCX3 in the hippocampus was downregulated after exposure to EtOH (except 10% EtOH for 30 days) and this inhibition was time and dose dependent with EtOH exposure. The level of p-Akt, which is an upstream regulation factor of NCX3, showed a trend similar to that of NCX3 protein. Chronic EtOH exposure reduced the expression of NCX3 in the hippocampus of male C57BL/6 mice, increasing intracellular calcium and apoptosis, resulting in spatial memory impairment in mice.